Dinamika Psikologis Generasi Z Dalam Minat Dan Partisipasi Politik Di Era Digital: Systematic Literature Review - Dinda Putri Andini; Raihana Ar santi; Sherli Meisiska; Khoiriya Ulfah (CV. ITTC INDONESIA, 2026)
This study examines the psychological dynamics of Generation Z in relation to their political interest and participation in the digital era through a Systematic Literature Review (Systematic Literature Review) approach. Generation Z, individuals born between 1997 and 2012, represents a strategically significant demographic group in Indonesian democracy, comprising more than 56 percent of total registered voters in the 2024 General Election. The method employed involved systematic literature searching across three academic databases, namely Google Scholar, Sinta, and Scopus, covering publications from 2021 to 2025, resulting in 20 final articles analyzed through narrative synthesis. The findings reveal that political self-efficacy and political literacy are the most dominant psychological factors influencing Generation Z's political engagement. Social media platforms, particularly TikTok, Instagram, YouTube, and Twitter, function as primary spaces for political information consumption, identity formation, and political expression. However, the digital political landscape also presents significant challenges, including disinformation, echo chambers, political apathy, and the phenomenon of clicktivism, wherein digital political activity remains superficial and symbolic. This study concludes that Generation Z possesses substantial potential to advance digital democracy, yet this potential requires support through strengthened digital literacy and political education. Collaboration among government, educational institutions, families, media, and civil society is essential to cultivate a healthy digital ecosystem that enables Generation Z to become critical, active, and responsible political citizens.